STUDI SIFAT FISIK DAN KIMIA TANAH HABITAT BAMBU DI DESA HULU BANYU KECAMATAN LOKSADO KABUPATEN HULU SUNGAI SELATAN - Noorhasanah Noorhasanah; Yudi Firmanul Arifin; Muhammad Muchtar Effendy (Jurnal Sylva Scienteae, 2020)
Bamboo is one of the Non-Timber Forest Products (NTFPs) which has meaning and an important role in people's lives, especially in rural areas. The aim of this research is to describe the physical and chemical properties of bamboo habitat in Hulu Banyu Village, Loksado Subdistrict, Hulu Sungai Selatan District. The method used in this research is survey method. The determination of the survey location was based on the finding of certain types of bamboo found in the location. The location of the sampling point was determined by purposive sampling to represent the state of the bamboo habitat. The parameters observed in this study are the physical and chemical properties of the soil. The physical properties of the soil include: soil texture, soil structure, bulk density, particle density, and soil moisture content. Soil chemical properties include: soil macro nutrients (N, P, K), soil pH, and Cation Exchange Capacity (CEC). Soil texture in bamboo habitat in Hulu Banyu Village, sandy clay, sandy clay, clay and clay sand. Granular soil structure. Nutrients of N and P at both locations are average. The K content in both locations is high. The CEC values in both locations were categorized as very high and the pH values in both locations were categorized as somewhat sour. The highest bamboo potential is sweet bamboo while the smallest bamboo potential is bamboo haur.Keywords ; Bamboo; physical properties of soil; chemical properties of soil